Psychometric features (factor structure, reliability and validity) of the student self-perceived employability scale in Iranian students - Hamid Abdi; Mohammad Javad Leiaghatdar (آموزش مهندسی ایران, 2018)
The purpose of this study was to determine the psychometric features (Factor structure, validity and reliability) of the student self-perceived employability scale that have 22 items which developed by Rothwell et al. (2008). This research was performed among 185 senior students of technical field in Isfahan University who selected with cluster sampling method. Exploratory factor analysis released 4 factors which generally explained 70.53% of the total variance. Furthermore confirmatory factor analysis of the structure model showed that four-factor structure of the questionnaire were significant. The result showed that internal consistency of the scale and the four factors were acceptable. The correlation of each item with total score was meaningful and ranged from 0.51 to 0.77. Convergent criterion validity coefficient between each of items of student self-perceived employability scale with the curriculum employability scale that was linked theoretically was also significant. Altogether, founding of this study showed that student self-perceived employability scale have an adequate reliability and validity among Iranian samples and can be used as a valid evaluation tool in higher education institutions. It is also possible to promote student self-perceived employability through appropriate educational programs.